Towards realization of high performance energy storage device: Nanostructuring CNT electrode - Mohd Abid, Mohd Asyadi Azam (2013)
This paper is about vertically-aligned single-walled carbon nanotube (VA-SWCNT) electrodes for a symmetric electrochemical capacitor using a simple ethanol-based CNT growth system. From the CNT direct growth technique, the electrode was easily prepared, and consequently assembled with ionic liquid as electrolyte. VA-SWCNTs were directly grown on conducting SUS 310S foils in which the binder material was not incorporated in the capacitor structure. This capacitor demonstrated excellent gravimetric capacitance and a high rate capability.